The role of hypoglycemia in the development of cardiovascular catastrophes (experience of clinical studies) - E. V Doskina; I. I Almazova; B. M Tanhilevich (КардиоСоматика, 2018)
According to the Clinical recommendations "Algorithms of specialized medical care for patients with diabetes mellitus", and receiving hypoglycemic therapy, it is advisable to start at a plasma glucose level